Newborn Care. Issue 4 (July 2022) - Simpson, Kathleen Rice
Abstract : Our special topics series on newborn care in this issue covers three important aspects of nursing care for babies: safe sleep in the hospital to promote safe sleep at home, the Eat, Sleep, Console protocol for babies with neonatal opioid withdrawal syndrome and a scoping review of the role of the gastrointestinal microbiome in colic. We hope you enjoy reading these articles about newborn care and are able to incorporate the information into your clinical practice.